MicroRNA-199a Inhibits Cellular Autophagy and Downregulates IFN-β Expression by Targeting TBK1 in Mycobacterium bovis Infected Cells - Wang, Jie; Hussain, Tariq; Yue, Ruichao; Liao, Yi; Li, Qiang; Yao, Jiao; Song, Yinjuan; Sun, Xin; Wang, Nan; Xu, Lei; Sreevatsan, Srinand; Zhao, Deming; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
The mechanism by which microRNAs (miRNAs) modulate innate immunity and autophagy has not been fully elucidated in Mycobacterium bovis (M. bovis) infections. In this study, we identified that miR-199a inhibited key innate immune responses and autophagy in murine macrophages infected with M. bovis. Using ex vivo and in vitro approaches we show that the expression of miR-199a was significantly increased during M. bovis infection. Furthermore, miR-199a suppressed autophagy and interferon-β (IFN-β) production by directly targeting TANK-binding kinase 1 (TBK1) mRNA in both J774a.1 and BMDM cells. Upregulation of miR-199a or TBK1 silencing (siTBK1) inhibited maturation of autophagosomes and increased M. bovis survival. Our results demonstrate that, by targeting of TBK1, miR-199a modulates innate immune responses and promote the intracellular survival and growth of M. bovis.